2017
DOI: 10.1155/2017/6347145
|View full text |Cite
|
Sign up to set email alerts
|

Effect of 2 Bleaching Agents with a Content of High Concentrated Hydrogen Peroxide on Stained 2 CAD/CAM Blocks and a Nanohybrid Composite Resin: An AFM Evaluation

Abstract: The aim of this study was to evaluate color stability of 3 restorative materials, discoloration ability of different solutions, efficacy of 2 office bleaching agents, and surface roughness and topography. Sixty specimens for Clearfil Majesty Esthetic (CME), Lava Ultimate (LU), and Vita Enamic (VE) were prepared. They were immersed into 3 staining solutions for 2 weeks and then they were bleached. According to the measured L⁎, a⁎, and b⁎ parameters described by CIELAB system, color changes (ΔE00), translucency … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
23
0
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 31 publications
(28 citation statements)
references
References 56 publications
3
23
0
2
Order By: Relevance
“…Thus, the second null hypothesis was accepted. However, in a previous study 19 which evaluated the effect of the same in-office bleaching agents on the surface roughness and topography of LU and VE, it has been reported that in-office bleaching agents caused alterations on the surface of these materials. However, as discussed above, subjecting the specimens to staining solutions before bleaching may have contributed to the differences observed with this study.…”
Section: Discussionmentioning
confidence: 98%
See 2 more Smart Citations
“…Thus, the second null hypothesis was accepted. However, in a previous study 19 which evaluated the effect of the same in-office bleaching agents on the surface roughness and topography of LU and VE, it has been reported that in-office bleaching agents caused alterations on the surface of these materials. However, as discussed above, subjecting the specimens to staining solutions before bleaching may have contributed to the differences observed with this study.…”
Section: Discussionmentioning
confidence: 98%
“…Sixty rectangular‐shaped specimens with the dimensions of 6 ± 0.3 × 7 ± 0.3 × 1.3 mm were prepared with the use of a low‐speed diamond saw (Micracut 201, Metkon®, Bursa, Turkey) for each material. The number of specimens was determined according to a statistical power analysis conducted by a software program (G*Power 3.1) with a statistical power of 80% and significance level of 0.05 (α) based on a previous study . The LU and VE specimens were first polished with a polishing disc system (Sof‐Lex XT discs, 3M ESPE, St. Paul, MN) with coarse, medium, fine, and superfine grain size, respectively.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…To determine the subjective errors in this study, the color determination and evaluation was performed using the spectrophotometer apparatus, which is currently the most accurate tool for discoloration measurement [18]. It is a more objective method than the eye method (in 93.3% of cases), with an accuracy rate higher than current techniques (33% higher) [19].…”
Section: Discussionmentioning
confidence: 99%
“…According to various studies, the internal and external factors associated with the patients' habits and medical history as well as the exposure time and concentration of the staining material may impact the color stability of the tooth and the restorative materials [22]. Color change in the composite resin restorations may be physiological, chemical, hydrophilic or hydrophobic reactions and may be caused by water absorption due to different reasons, such as composition (optical primer, actuator, resin matrix, and fillers).…”
Section: Discussionmentioning
confidence: 99%